Quantitative Analysis for Decision Makers - Wisniewski, Mik (Pearson International Content, 2025)
Help your students understand how quantitative analysis supports effective management decision-making in today's fast-moving world Quantitative Analysis for Decision Makers, 8th Edition, by Wisniewski, Shafti and Yeo provides an accessible introduction to the quantitative methods of analysis that are routinely used across the public and private sectors to support effective management decision making. Adopting a learning-by-doing approach throughout, the text provides a clear explanation of each technique illustrating their practical application with the use of real data sets and with examples from government bodies and prominent businesses, including Google, Marks & Spencer, Tesla, Netflix, WWF and many more. The text is suitable for business and management undergraduate and postgraduate students and for MBA students taking a quantitative course as part of their studies. The new edition offers: Updated case illustrations from global business organisations like Tesla, Netflix, WWF, Google, Unilever Extended discussion of how artificial intelligence (AI) impacts on quantitative analysis and decision making. Updated ‘QADM in action’ case studies illustrating how organisations benefit from the use of analytical techniques in the real world. Coverage of recent developments such as Big Data and business analytics; multi-criteria decision analysis and data mining; agent-based simulation; data visualisation. Examples and cases have been updated to reflect global events such as the Covid pandemic and geopolitical uncertainties. Fully worked examples and exercises supported by Excel data sets to show how to approach a particular problem using the techniques About the authors: Mik Wisniewski has almost five decades of experience in Quantitative Analysis. He has taught at a number of leading universities, worked in both industry and government and has extensive consultancy experience in the UK and across Europe, Africa, the Middle East and Asia. Dr Farhad Shafti is a sen